2020
DOI: 10.1007/s10208-020-09453-0
|View full text |Cite
|
Sign up to set email alerts
|

On the Complexity Exponent of Polynomial System Solving

Abstract: We present a probabilistic Las Vegas algorithm for solving sufficiently generic square polynomial systems over finite fields. We achieve a nearly quadratic running time in the number of solutions, for densely represented input polynomials. We also prove a nearly linear bit complexity bound for polynomial systems with rational coefficients. Our results are obtained using the combination of the Kronecker solver and a new improved algorithm for fast multivariate modular composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…More precisely, we make use of the recent work of Safey El Din and Schost [61], who take into account multi-homogeneity and provide estimates on the height of the representations and the bit complexities of their algorithms. Note that as this work reached completion, a new preprint by van der Hoeven and Lecerf [66] appeared that points to the possibility of improving further the exponent of d n in our results, while retaining the same approach. The Kronecker representation, and similar constructions, have also appeared in the literature under the name 'rational univariate representation' [60,5].…”
Section: Previous Workmentioning
confidence: 66%
“…More precisely, we make use of the recent work of Safey El Din and Schost [61], who take into account multi-homogeneity and provide estimates on the height of the representations and the bit complexities of their algorithms. Note that as this work reached completion, a new preprint by van der Hoeven and Lecerf [66] appeared that points to the possibility of improving further the exponent of d n in our results, while retaining the same approach. The Kronecker representation, and similar constructions, have also appeared in the literature under the name 'rational univariate representation' [60,5].…”
Section: Previous Workmentioning
confidence: 66%
“…An important application of the present results concerns polynomial system solving, for which we prove new complexity bounds in [28]: the key algorithms are the Kronecker solver [14] and fast multivariate modular composition. For the latter problem, we mostly follow the strategy deployed in the proof of Proposition 5.7.…”
Section: Discussionmentioning
confidence: 88%
“…The new complexity bounds for multi-point evaluation are also crucial for our new bit complexity bounds for multivariate modular composition and the application to polynomial system solving in [28]. Section 7 addresses the special case when is a field of small positive characteristic p. We closely revisit the method proposed in [34, section 6], and again make the complexity bound more explicit.…”
Section: Contributionsmentioning
confidence: 99%
“…This problem naturally relates to several areas of applied algebra, including polynomial system solving, since we may use it to verify whether all points in a given set are solutions to a system of polynomial equations. In [16], it has even be shown that efficient algorithms for multi-point evaluation lead to efficient algorithms for polynomial system solving. As an other more specific application, bivariate polynomial evaluation intervenes in computing generator matrices of geometric error correcting codes [20].…”
Section: Introductionmentioning
confidence: 99%